The role of and challenges facing non-governmental organizations in the environmental impact assessment process in Punjab, Pakistan. Issue 1 (2nd January 2020) - Khan, Mehreen; Chaudhry, Muhammad Nawaz; Ahmad, Sajid Rashid; Saif, Samia
ABSTRACT: Considering the ineffective environmental impact assessment (EIA) process and limited public participation, it is important to evaluate the role played by informal regulators like Non-Governmental Organizations (NGOs) in EIA in raising the voice of communities and promoting sustainable development. This study aims to identify the NGOs that are involved in the EIA process in Punjab. It also aims to evaluate how effectively the NGOs play their roles as watchdog, information provider and pressure group as well as discuss the challenges they face in EIA. Semi-structured interviews are used as a data collection method. Results of the study revealed that very few NGOs are involved in the EIA process. The role of NGOs as watchdog is not prominent because they are rarely involved in public participation and scoping. Only one international NGO has played a key role as an information provider. Some local NGOs functioned as pressure groups against environmentally damaging development projects. The key challenges faced by NGOs include lack of financial and technical resources and support from the state and society.